Fluid pressurisation and earthquake propagation in the Hikurangi subduction zone - S. Aretusini (Nature Portfolio, 2021)
Laboratory experiments reproducing earthquake slip in non cohesive fault rocks under fluid pressurised conditions are challenging. Thanks to these experiments, the authors show that earthquake slip occurring in tsunamigenic subduction zone faults is controlled by dilatancy and pressurisation processes.